PENGUATAN DESA WISATA MELALUI INOVASI PRODUK OLAHAN PANGAN LOKAL SUBOPTIMAL DI DESA BONJERUK, LOMBOK TENGAH - Baiq, Santi Rengganis; Fathurrahman, Fathurrahman; Baiq Diah Fitasari; Fadilla Fajri; Haekal Ashari (Yayasan Nusantara Hasana Berdikari, 2025)
The development of Bonjeruk Tourism Village based on local food is a strategy to utilize the village’s culinary wealth as a tourism attraction, while simultaneously strengthening cultural identity and fostering community economic growth. This community service program aims to enhance production and diversify suboptimal local food to support local businesses, as well as to improve partners’ capacity through soft-skill training, product packaging training, and strengthening the tourism village institution. The implementation method consisted of five stages: program socialization, training, technology and innovation application, mentoring and evaluation, and sustainability planning. The results indicate a high level of technology adoption, with the use of noodle-making equipment reaching 90%, and 100% community participation in every stage of the program. The developed local food products include mie ayam merangkat, roti merangkat, kombucha probiotic beverages, and pumpkin bread, which have been promoted as the culinary identity of Bonjeruk Tourism Village. Product packaging training also contributed to value addition by creating attractive designs that meet market standards. The outcomes of this program include improved community skills, the creation of distinctive village products as souvenirs, and the strengthening of the tourism village institution. Overall, this program contributes to the sustainable development of Bonjeruk Tourism Village through the downstreaming of local food products.